2017
DOI: 10.1017/s1751731117000660
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the CP content in broiler feeds: impact on animal performance, meat quality and nitrogen utilization

Abstract: Reducing the dietary CP content is an efficient way to limit nitrogen excretion in broilers but, as reported in the literature, it often reduces performance, probably because of an inadequate provision in amino acids (AA). The aim of this study was to investigate the effect of decreasing the CP content in the diet on animal performance, meat quality and nitrogen utilization in growing-finishing broilers using an optimized dietary AA profile based on the ideal protein concept. Two experiments (1 and 2) were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
83
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 29 publications
16
83
3
1
Order By: Relevance
“…This example unequivocally demonstrates the potential synthetic and crystalline amino acids hold as alternatives to soybean meal in chicken-meat production and is supported by another recent study [37]. Nevertheless, CP reductions of this magnitude may compromise the efficiency of feed conversion with associated increases in fat deposition [38][39][40][41]. The genesis of compromised feed conversion ratios (FCRs) probably stems, at least partially, from an insufficiently accurate identification of essential and non-essential amino acid requirements, or ideal protein ratios, in the context of reduced-CP diets.…”
Section: Reduced-crude Protein Dietssupporting
confidence: 63%
“…This example unequivocally demonstrates the potential synthetic and crystalline amino acids hold as alternatives to soybean meal in chicken-meat production and is supported by another recent study [37]. Nevertheless, CP reductions of this magnitude may compromise the efficiency of feed conversion with associated increases in fat deposition [38][39][40][41]. The genesis of compromised feed conversion ratios (FCRs) probably stems, at least partially, from an insufficiently accurate identification of essential and non-essential amino acid requirements, or ideal protein ratios, in the context of reduced-CP diets.…”
Section: Reduced-crude Protein Dietssupporting
confidence: 63%
“…In addition to optimizing feeding strategies for growth requirements, nitrogen utilization and excretion requires consideration due to the environmental impacts of ammonia on bird health and overall sustainability. Several studies have demonstrated that reducing CP has a significant impact in reducing nitrogen excretion (Aletor, Hamid, Nieß, & Pfeffer, 2000;Belloir et al, 2017;Bregendahl, Sell, & Zimmerman, 2002). One study reported that reducing CP, by as little as 1%, can have up to a 13% decrease in nitrogen excretion (Belloir et al, 2017).…”
Section: Dietary Protein and Ammonia Metabolismmentioning
confidence: 99%
“…Several studies have demonstrated that reducing CP has a significant impact in reducing nitrogen excretion (Aletor, Hamid, Nieß, & Pfeffer, 2000;Belloir et al, 2017;Bregendahl, Sell, & Zimmerman, 2002). One study reported that reducing CP, by as little as 1%, can have up to a 13% decrease in nitrogen excretion (Belloir et al, 2017). While the reduction of CP may benefit production from an environmental perspective, diets must be carefully formulated to avoid negative impacts on broiler growth (Aletor et al, 2000;Bregendahl et al, 2002).…”
Section: Dietary Protein and Ammonia Metabolismmentioning
confidence: 99%
“…Différentes approches nutritionnelles déjà existantes pour d'autres espèces ou productions pourraient ainsi avoir un intérêt en production de poulets LR, par exemple l'alimentation séquentielle, qui permet, en outre, d'utiliser de façon directe des céréales produites sur l'exploitation (Umar Faruk et al 2010), ou encore l'alimentation de précision, qui permet d'apporter des rations parfaitement adaptées aux besoins des animaux (Andretta et al 2016), même si pour cette dernière approche, des efforts de recherche sont encore nécessaires pour l'adapter aux spécificités des volailles (gestion à l'échelle du lot, mesure régulière du poids et de la consommation, modèles de prédiction des besoins). Enfin, l'utilisation d'acides aminés de synthèse permet également d'envisager la réduction du taux protéique des rations distribuées aux poulets de chair, sans dégradation des performances et avec des conséquences positives, sur l'excrétion azotée notamment (-13% par point de protéines, Belloir et al 2017).…”
Section: / Quels Leviers Pour Renforcer Les Services Et Réduire Les Aunclassified